Analyzing Relationship between Safety Climate and Safety Leadership in a Phosphoric Acid Industry - Nia Tri Wulandari; Dayinta Annisa Syaiful; Endang Dwiyanti; Sovia Rahmania Warda (Universitas Airlangga, 2022)
Introduction: Safety-based leadership style has a positive relationship with the workplace safety climate in a company. Transactional leadership has a direct positive relationship with work safety participation and has an indirect relationship with work safety climate. In a phosphoric acid industry especially in 2019, the achievement of sulfuric acid production decreased from 2019 to 2020. The gap range was caused by leadership factors. This study has an objective to analyze the overview of safety climate based on safety leadership in the phosphoric acid industry. Methods: This research used a cross-sectional quantitative survey. The respondents comprised of 44 personnel. The independent factors in this investigation were the dimensions of leadership style and the dependent variable in this study wasthe condition of the work safety climate in each work group in the creation unit. The analysis used NOSACQ-50 radar plot analysis. Results: Of all perceptions of consideration leadership style, eitherin the high, very high, or enough categories, the dimension of work safety justice had the lowest score. The highest dimension of work safety climate was in the dimension of management safety priority and ability, especially in the perception of a high and very high initiating structure leadership style. Conclusion: A very high perception of the consideration leadership style had a work safety climate that had a higher score when compared to the high and sufficient perception. The highest dimension of work safety climate was in the dimensions of management safety priority and ability, especially in the perception of a high and very high initiating structure leadership style.